Comparison of Financial Distress Predictions With Altman, Springate, Zmijewski, and Grover Models - Martini, Rita; Raihana Aksara, Rana; Rachma Sari, Kartika; Zulkifli, Zulkifli; Hartati, Sukmini (Manunggal Halim Jaya, 2023)
Several predictive models of financial distress and corporate bankruptcy have been developed. In this study, the Altman model (Z-Score), the Springate model (S-Score), the Zmijewski model (X-Score), and the Grover model (G-Score) were used. These methods are used to analyze the potential for financial difficulties which in the end to determine the potential for bankruptcy at PT Garuda Indonesia (Persero) Tbk. The secondary data used is in the form of financial statements for 2018-2020. The results of the bankruptcy prediction using the Altman model resulted in PT Garuda Indonesia (Persero), Tbk being in the bankrupt area, which experienced financial difficulties in 2018 to 2020. The Springate model was in a distress position and went bankrupt in 2018 and 2020, while in 2019 is in the gray area. Then the Zmijewski model is in a state of bankruptcy, which is experiencing financial difficulties and has the potential to go bankrupt in three years. Grover's model shows the company was in a state of bankruptcy in 2018 and 2020, and safe in 2019.